2013
DOI: 10.2527/jas.2012-6200
|View full text |Cite
|
Sign up to set email alerts
|

Genetic correlations between lactation performance and growing-finishing traits in pigs

Abstract: Genetic selection for increased litter size of sows increases the risk of a large negative energy balance during lactation. Furthermore, the feed intake capacity of the lactating sows might be reduced due to the simultaneous selection for greater feed efficiency during the growth phase when sows were actually reared as finishers but later on selected for breeding. There is a need to improve lactation performance of sows and continue selection for feed efficiency of grower-finishers in commercial breeding. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 15 publications
6
31
0
2
Order By: Relevance
“…The genetic correlation between FEED and LW was also positive but imprecise (r g = 0.33, PSD = 0.20). Bergsma et al (2008) and Bergsma et al (2013) estimated similar genetic correlations between feed intake during lactation and litter weight gain (0.48 and 0.58). Sows with good appetite have a genetic potential for producing heavy litters.…”
Section: Correlationsmentioning
confidence: 69%
See 2 more Smart Citations
“…The genetic correlation between FEED and LW was also positive but imprecise (r g = 0.33, PSD = 0.20). Bergsma et al (2008) and Bergsma et al (2013) estimated similar genetic correlations between feed intake during lactation and litter weight gain (0.48 and 0.58). Sows with good appetite have a genetic potential for producing heavy litters.…”
Section: Correlationsmentioning
confidence: 69%
“…The estimated heritabilities for appetite during the first 3 weeks (APP; h 2 = 0.07, PSD = 0.03) and for feed intake at 3 weeks (FEED; h 2 = 0.06, PSD = 0.03) were, however, lower than estimates previously presented in the literature. Bergsma et al (2008) estimated the heritability for voluntary feed intake during the whole lactation period at 0.30, Gilbert et al (2012) at 0.26 and Bergsma et al (2013) at 0.23. Bunter et al (2010) reported a heritability of average lactation feed intake at 0.15, and Hermesch et al (2010) estimated the heritability at 0.10 during early lactation (5 to 14 days).…”
Section: Heritabilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the present study confirm the observations of Vinsky et al (2006) and Patterson et al (2011) that hyper-prolific sows, despite experimentally restricted-fed to 50% of the expected voluntary intake and extensive body tissue catabolism, presented estrus almost immediately after weaning and acceptable farrowing rates after breeding. This may be partially due to the genetic selection against weaning-to-estrus interval (Vinsky et al, 2006;Bergsma et al, 2013). However, although energy balance may become positive after weaning, sows with rapid return to estrus may not have fully recovered from the damages caused by catabolism during lactation, with possible negative impacts on follicle and embryo quality, and consequently on the size and quality of the next litter (Quesnel et al, 2007;Quesnel, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…A farm may, for example, consist of units of 8-12 groups each, which introduces the risk of confounding environmental unit or unit  batch effects with IGEs, even when random group effects are included in the statistical model. Compared with a previous study (Bergsma et al, 2008), Bergsma et al (2013), for example, found substantially smaller IGEs in growth rate in domestic pigs due to an increase in the data set and a change in the statistical model.…”
Section: Estimating Igesmentioning
confidence: 99%